Panaitopol-Bandila-Lascu Type Inequalities for Generalized Hyperbolic Functions - Nantomah, Kwara; Kasimu, Osman (Asian Research Journal of Mathematics, 2020)
In this paper, we establish Panaitopol-Bandila-Lascu type inequalities for some generalized hyperbolic functions. The established results extend and generalize some earlier results due Barbu and Piscoran. The procedure makes use of the classical arithmetic-geometric mean inequality and the Cauchy-Schwarz inequality.